2012
DOI: 10.1787/9789264116917-en
|View full text |Cite
|
Sign up to set email alerts
|

OECD Reviews of Evaluation and Assessment in Education: New Zealand 2011

Abstract: This work is published under the responsibility of the Secretary-General of the OECD. The opinions expressed and arguments employed herein do not necessarily reflect the official views of OECD member countries. This document and any map included herein are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area. You can copy, download or print OECD content for your own use, and you can inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 0 publications
0
54
0
9
Order By: Relevance
“…Source: Nusche, D. et al (2012), OECD Reviews of Evaluation and Assessment in Education: New Zealand, http:// dx.doi.org/10.1787/9789264116917-en. 127 immigrant/cultural/linguistic background, parental level of education, occupation and income level (OECD, 2013b).…”
Section: Pay Special Attention To Monitoring the Learning Outcomes Ofmentioning
confidence: 99%
“…Source: Nusche, D. et al (2012), OECD Reviews of Evaluation and Assessment in Education: New Zealand, http:// dx.doi.org/10.1787/9789264116917-en. 127 immigrant/cultural/linguistic background, parental level of education, occupation and income level (OECD, 2013b).…”
Section: Pay Special Attention To Monitoring the Learning Outcomes Ofmentioning
confidence: 99%
“…To cover a broad range of items without overburdening individual students, three different groups of students are created for each subject, with each group being tested on one third of the tasks. The tasks are not necessarily related to particular year levels -many tasks are the same for Grade 4 and Grade 8 students (Nusche et al, 2012).…”
Section: Build An Integrated Ict Infrastructure and Visionmentioning
confidence: 99%
“…Among the schools with few inclusive practices, weaknesses included poor assessment of student progress and insufficient monitoring of the teaching provided for students with high needs. The review identified a set of good practices related to the assessment of students with high needs which are likely to be relevant for Danish schools also (Nusche et al, 2012):…”
mentioning
confidence: 99%
“…Two key resource documents Narrative Assessment: A Guide for Teachers and The New Zealand Curriculum Exemplars for Learners with Special Education Needs are available to support teachers in maximising learning opportunities and pathways for children with special educational needs (Nusche et al, 2012). The development of such tools to support schools, teachers and school leaders to monitor the learning outcomes of students with special needs is also an option for Denmark.…”
mentioning
confidence: 99%
See 1 more Smart Citation